2012
DOI: 10.1039/c2cc32834h
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic nanoparticles of precise microstructure polyolefins

Abstract: Nanoparticles of precisely branched polyethylenes possess a distinct oblate shape resulting from a crystalline lamella in the particle as revealed by SAXS and TEM, and display controllable and well-behaved thermal behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, discriminating between growth and nucleation in the Avrami equation is not straightforward, and the intensity of the supercooling at high degree of confinement remains the best proof of the occurrence of homogeneous nucleation. Recently, extremely large supercooling of PE single lamellae has been achieved. , The authors observed that the crystallization temperature evolved as a function of the crystal thickness. The relationship between the crystallization temperature and the crystal thickness was given by Strobl and implies the existence of an intermediate phase (mesomorphic phase) along the crystallization pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, discriminating between growth and nucleation in the Avrami equation is not straightforward, and the intensity of the supercooling at high degree of confinement remains the best proof of the occurrence of homogeneous nucleation. Recently, extremely large supercooling of PE single lamellae has been achieved. , The authors observed that the crystallization temperature evolved as a function of the crystal thickness. The relationship between the crystallization temperature and the crystal thickness was given by Strobl and implies the existence of an intermediate phase (mesomorphic phase) along the crystallization pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extremely large supercooling of PE single lamellae has been achieved. 33,34 The authors observed that the crystallization temperature evolved as a function of the crystal thickness. The relationship between the crystallization temperature and the crystal thickness was given by Strobl and implies the existence of an intermediate phase (mesomorphic phase) along the crystallization pathway.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this regard polyethylene (PE) is of particular interest, since it is the prototype of a crystalline polymer and its crystallization behavior has been studied intensely in the past . Different methods have been developed for the synthesis of anisotropic PE single crystal nanoparticles with variable size and shape, such as insertion polymerization of ethylene in aqueous surfactant solution, free-radical emulsion polymerization at intermediate pressures, crystallization of the hydrophobic core of micelles formed from diblock copolymers with a PE and a hydrophilic block, self-assembly of linear ethylene–acrylic acid copolymers in aqueous solution, and crystallization of precisely branched linear polyethylene in nanoscale droplets . An analysis of such nanoparticles composed of linear polyethylene by a combination of cryo-TEM and SAXS revealed these to be polymer single crystals composed of one lamella and with an extension of only a few tens of nanometers also in the lateral direction (cf.…”
Section: Introductionmentioning
confidence: 99%